Effectiveness of advance directives for the care of terminally ill patients in Chiang Mai University Hospital, Thailand - Sudarat Sittisombut (2018)
The key hypothesis behind advance directives (ADs) proposes that, if an intervention enhances a person's right to choose, a dying person will not opt for expensive, life-prolonging medical care and an ethically acceptable saving of resources will result. In order to assess the acceptability and effectiveness of ADs in reducing cardiopulmonary resuscitation (CPR) attempts and in-hospital death among terminally ill patients in a tertiary care hospital in northern Thailand, a non-randomized, controlled intervention study using an after-only unequivalent control group design was conducted. The majority of the subjects and the surrogates preferred to employ ADs in expressing their preferences on CPR and there was a high level of agreement between the subjects and surrogates on the decision. The use of ADs appeared to be effective in reducing futile CPR attempts and the in-hospital mortality rate among subjects during the index hospitalization. Advance directives were accepted well in this study setting. © 2008 The Authors Journal Compilation © 2008 Blackwell Publishing Asia Pty Ltd.